Forage legumes for improved fallows in agropastoral systems of subhumid West Africa. III. Nutrient import and export by forage legumes and their rotational effects on subsequent maize - Muhr, L.; Tarawali, Shirley A.; Peters, Michael; Schultze-Kraft, Rainer (1999)
In a short-term improved fallow for crop-livestock farming systems of subhumid west Africa, rotational effects from a range of forage legumes on a subsequent maize crop were studied at two sites in south-west Nigeria. Nutrient (nitrogen, phosphorus and potassium) export from the fallows in the form of dry season herbage and subsequent nutrient accumulation in the green manure biomass were correlated with growth patterns of maize subsequently grown on the legume plots. Maize plant height, grain yields and nitrogen content were compared to the response of maize to nitrogen fertiliser after natural fallow. Up to 120 kg/ha N, 10 kg/ha P and 135 kg/ha K were removed as dry season herbage. Thereafter, within four months of regrowth, up to 144 kg/ha N, 18 kg/ha P and 140 kg/ha K were accumulated to incorporate as green manure before planting a maize crop. Maize grain yield increases due to preceding legumes ranged between 0% and 52% or 147% depending on the sites which showed contrasting fertiliser nitrogen responses for maize grain yield. Nutrient export in legume fallow biomass removed in the breeding dry season apparently did not influence the subsequent yield response of maize. Significant relationships between rotational effects and patterns of green manure nitrogen release were found only at the site with lower fertiliser nitrogen response. Thus, the high potential of forage legumes to improve subsequent crop growth is influenced by site differences and is not determined by nutrient contribution alone.